2018
DOI: 10.1016/j.seizure.2018.11.004
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of onchocerciasis-associated epilepsy in villages in Maridi County, Republic of South Sudan: A community-based survey

Abstract: Highlights An epilepsy prevalence of 4.4% was observed in villages in Maridi. Living close to the Maridi river is a major risk factor for epilepsy. Persons with nodding seizures and with other forms of epilepsy live in the same areas. Ivermectin coverage needs to increase to prevent onchocerciasis associated epilepsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
115
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 93 publications
(150 citation statements)
references
References 23 publications
10
115
7
Order By: Relevance
“…More recent studies have reported nodding seizures among persons with epilepsy (PWE) in the onchocerciasis-endemic regions in Cameroon [10] and the Democratic Republic of Congo [11]. A high prevalence of epilepsy has also been reported in many onchocerciasis meso-and hyper-endemic regions [12][13][14][15] particularly where transmission is poorly controlled [16][17][18][19]. A study in an onchocerciasis-endemic region in the Mbam valley in Cameroon showed that the risk of developing epilepsy increased with increasing O. volvulus microfilarial density [20].…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies have reported nodding seizures among persons with epilepsy (PWE) in the onchocerciasis-endemic regions in Cameroon [10] and the Democratic Republic of Congo [11]. A high prevalence of epilepsy has also been reported in many onchocerciasis meso-and hyper-endemic regions [12][13][14][15] particularly where transmission is poorly controlled [16][17][18][19]. A study in an onchocerciasis-endemic region in the Mbam valley in Cameroon showed that the risk of developing epilepsy increased with increasing O. volvulus microfilarial density [20].…”
Section: Introductionmentioning
confidence: 99%
“…In spite of this, we recently observed in South Sudan that certain PWE were not given ivermectin because the community considered that PWE should not take ivermectin. In villages in Maridi County in 2017, only 25.6% of PWE were treated with ivermectin [24] while the overall ivermectin coverage in persons above the age of 11 years was 50-60% [25]. Lower coverage among PWE compared to the general population has also been reported in Cameroon [26].…”
Section: Discussionmentioning
confidence: 99%
“…In onchocerciasis-endemic regions with high-ongoing or recent O. volvulus transmission, it is common to find households where there are several children with epilepsy, especially in families who reside and/ or farm close to blackfly breeding sites (Boussinesq et al 2002;Colebunders et al 2018b). The fact that clustering of PWE has been reported among distant, unrelated onchocerciasis-endemic communities makes it unlikely that this is due to a genetic cause.…”
Section: Qualitative Researchmentioning
confidence: 99%